Survey on Human Resource Management Practices In Private Sector In India: Exploring the Impact of Service Quality on Firm Performance (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Itis difficult for service firms to envision and understand the aspects whichmean high quality to consumers. Service quality allows an organization todifferentiate itself from the competitors and gain a substantial competitiveadvantage. Hence,service quality is at the forefront of both the marketing literature in generaland the service marketing literature in particular (Lassar et al., 2001). Quality service isrecently considered a critical factor that enables many service organizationsachieve a differential advantage over their competitors. It has become animportant research topic because of its important relationship to corporatemarketing, financial performance, and moreover firm performance.